GE_GERICHTE P/6506/2016 vom 30. August 2018 - GE Cour de justice (2018)
LÉSION CORPORELLE SIMPLE ; MENACE(DROIT PÉNAL) ; DANCING ; AGENT DE SECURITE ; VICTIME ; CRÉDIBILITÉ ; TORT MORAL | CP.123; CP.180; CPP.10.al2; CPP.122; CO.47; CO.49; CPP.429